Understanding uncertainty - Lindley, D. V. (Dennis Victor), 1923-2013. (Hoboken, N.J. : Wiley, 2013)
'We want you to face up to uncertainty, not hide it away under false concepts, but to understand it and, moreover, to use the recent discoveries so that you can act in the face of uncertainty more sensibly than would have been possible without the skill.'--Dennis Lindley Accessibly written at an elementary level, this outstanding text examines uncertainty in various everyday situations and introduces readers to three rules that prove uncertainty can be handled with as much confidence as ordinary logic. Combining a concept of utility with probability, the book insightfully demonstrates how uncertainty can be measured and used in everyday life, especially in decision-making and science. Completely reformatted and visually easy to read, this revised edition includes new material on the computational influence and breakthroughs of hierarchical Bayesian methods and inference; betting (Efron's dice); and the current recession; as well as additional illustrations, updated references, and simplified writing for clarity, ease of continuity and research.
Title from resource description page (Recorded Books, viewed November 21, 2013).
Keywords: Mathematics; Electronic books